Considerations for Pregnant Dental and Health Care Workers amid COVID-19. (October 2020) - Mann, A.; Dahiya, A.; Souza, L.C.; Letra, A.
Introduction: Coronavirus disease 2019 (COVID-19) is a highly contagious disease that quickly reached pandemic levels. Over 5 million COVID-19 cases and approximately 330, 000 deaths have been recorded worldwide. Transmission is primarily spread through direct, indirect (through contaminated objects or surfaces), or close contact with infected people via respiratory droplets, the mouth, and/or nose secretions. Health care professionals (HCPs), including dental HCPs, are recognized to be at considerably high risk for infection due to the close proximity to patients and aerosol-generating procedures. During pregnancy, HCPs may be at even higher risk since pregnancy substantially increases the susceptibility to infectious diseases. Objectives: Here, we present the posed risks and potential effects of COVID-19 on maternal and fetal health. Current prevention and management strategies for COVID-19 on pregnant dental and HCPs are also discussed. Results: Significant progress is being made in understanding the pathogenesis and clinical consequences of COVID-19. Pregnant women are affected more adversely with viral illnesses, although evidence of vertical transmission of COVID-19 is controversial. Based on the presence of atypical symptoms, the significant numbers of asymptomatic individuals who are COVID-19 positive, and the high susceptibility to viral diseases observed in pregnant women, recommendations have been put forth to limit the exposure of COVID-19–positive or even suspected cases to pregnant HCPs, and these are likely to evolve as new information becomes available. Conclusion: Pregnant HCPs require extra caution: not only are they considered a high-risk population, but their work at the frontline in a pandemic may expose them to additional risks. Complete awareness of the effects of COVID-19 on maternal and fetal/infant health, as well as prevention and management guidelines for pregnant HCPs, will allow for a safer work environment. Health care institutional policies aimed at protecting pregnant HCPs should consider avoiding their assignment as first responders, especially if equally trained staff are available. Knowledge Transfer Statement: Dental and health care professionals can use the information in this review to improve their awareness of COVID-19 risks, signs, and symptoms and the associated effects on the health of pregnant health care professionals and their unborn/newborn children.